3D hierarchical CuO/Co3O4 core–shell nanowire array on copper foam for on-demand hydrogen generation from alkaline NaBH4 solution. Issue 91 (16th September 2016) - Xie, Lisi; Wang, Kunyang; Du, Gu; Asiri, Abdullah M.; Sun, Xuping
Abstract : A 3D hierarchical CuO/Co3 O4 core–shell nanowire array works as a robust and highly active catalyst toward the hydrolytic dehydrogenation of NaBH4 for on-demand hydrogen generation in alkaline solutions. Abstract : In this work, we demonstrate the first use of a 3D hierarchical CuO/Co3 O4 core–shell nanowire array in situ grown on copper foam as a robust and highly active catalyst toward the hydrolytic dehydrogenation of NaBH4 for on-demand hydrogen generation in alkaline solutions. This monolithic catalyst exhibits a maximum hydrogen generation rate of 6162.55 mL min −1 g(CuO/Co3 O4 ) −1 under ambient conditions, which is higher than that of most reported Co-based catalysts, with an activation energy of 56.38 kJ mol −1 . It also shows good durability and reusability and can be used as an on/off switch for on-demand hydrogen generation.